Numerical study and performance correlation development on counter-flow indirect evaporative air coolers. (December 2017) - Wan, Yangda; Ren, Chengqin; Wang, Zhao; Yang, Yang; Yu, Lei
Highlights: The effects of the various dimensionless factors on counter-flow IEC are studied. The mathematical model developed is validated against published data. A performance correlation for the IEC is developed. The correlation will provide a useful tool to predict the performance of the IEC. Abstract: In this paper, a numerical study of heat and mass transfer in counter-flow indirect evaporative air coolers is presented using an approach proposed by previous work. The mathematical model equations of continuity, momentum, energy and concentration are solved by the finite volume method to obtain the value of primary outlet dimensionless temperature. This mathematical model developed is validated against published data acquired from literature. The key target of presented analysis is to develop a performance correlation based on five dimensionless factors: ratio of channel length to half width of secondary air channel, ratio of water to secondary air mass flow rate, primary air inlet Reynolds number, secondary air inlet dimensionless temperature and water film inlet dimensionless temperature. Numerical simulations are performed by changing the value of each dimensionless factor under a constant value for other parameters. The simulation results are regressed to obtain the empirical constants of the correlation. The value of outlet dimensionless temperature is varied from 0.47 to 0.92. The developed correlation can predict the performance of the counter-flow indirect evaporative air coolers within a discrepancy of 12.6%. The correlation would be helpful to provide a simpler equation to improve the calculation speed within the engineering allowable accuracy range.